Good-Life Concepts of Moral Value in Robin Hood Movie - Yusuf, Faidah; Fachrunnisa, Ince (Universitas Negeri Semarang, 2021)
The study aims to know good-life concepts of moral value in Robin Hood movie. This research used qualitative approach. The researcher found that five moral principles are tolerance, belief, kind-hearted, integrity, and responsibility. In this movie, good-live concepts of moral value are tolerance for human relationships with Heaven, belief is entrusting everything to God's power, kindâ€hearted is honesty in this movie that the hero succeeded in winning people's hearts by his supporting honesty, integrity is like finding a valuable gem, and responsibility portrayed feels responsible for defense, reminding people of responsibility to protect their position in everywhere.